Analisis Pengaruh Leverage, Average Collection Period, Sales Growth dan Profitabilitas Terhadap Financial Distress - Annisa Citra Wulandari; Reni Oktavia; Ade Widiyanti; A. Zubaidi Indra (Goodwood Publishing, 2022)
This research was conducted to empirically test the effect of the independent variable on the dependent variable. In this study, the independent variables used are leverage, average billing period, sales growth and profitability, while the dependent variable is financial distress proxied by Interest Coverage Ratio (ICR). The population used in this study is the food and beverage sector which is listed on the Indonesia Stock Exchange (IDX) in 2015-2019. The method used is purposive sampling in the form of 125 samples. The type of data used is secondary data. File investigation using descriptive statistics and logistic regression analysis with SPSS 26 software. The conclusion of this study is that leverage, profitability, and the average billing period have a positive effect on financial distress, while sales growth has no effect on financial distress.